2018
DOI: 10.1080/23744731.2018.1490130
|View full text |Cite
|
Sign up to set email alerts
|

Experimental analysis of mixing ventilation efficiency using a vortex diffuser: Comparison to a lobed multicone diffuser

Abstract: In a recent work, an innovative multi-cone diffuser integrating lobed inserts as vortices promoters was proposed, and was compared to its counterpart without lobed inserts. The former offers better mixing of the jet with the ambient air, and significantly improves thermal comfort. In this study, the innovative diffuser is compared to a vortex diffuser under the same experimental conditions. The vortex diffuser is described in the scientific and technical A c c e p t e d M a n u s c r i p t literature as the be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…While in the case of cooling, the pollutant removal rate was not well as MV often leaded to dead corners where clean air could not reach. The solution of increasing air flow rate would cause new problems, such as loud noise and high energy consumption [ 21 ]. In addition, MV had a higher risk of airborne infectious diseases, especially in the era of COVID-19.…”
Section: Categories Of Different Ventilation Modesmentioning
confidence: 99%
“…While in the case of cooling, the pollutant removal rate was not well as MV often leaded to dead corners where clean air could not reach. The solution of increasing air flow rate would cause new problems, such as loud noise and high energy consumption [ 21 ]. In addition, MV had a higher risk of airborne infectious diseases, especially in the era of COVID-19.…”
Section: Categories Of Different Ventilation Modesmentioning
confidence: 99%
“…Mixing ventilation, which is most widely used in modern buildings, relies on the dilution method to optimize thermal comfort, improve energy efficiency and enhance the movement of fresh air [73]. These considerations are particularly important in the cooling mode, where thermal discomfort, the presence of dead pockets in the occupied zone and noise are frequently reported [74]. Mechanical ventilation can also generate drafts.…”
Section: Mechanical Ventilationmentioning
confidence: 99%
“…This type of draft affects the entire body, but causes discomfort mainly at head and neck level [75]. The geometry and location of the supply nozzle are critical for achieving optimal air velocity, direction of flow and the proportions in which fresh air is mixed with stale air [74]. Various supply nozzles for mechanical ventilation systems have been described in the literature [76,77].…”
Section: Mechanical Ventilationmentioning
confidence: 99%
“…They stated that the duct length was reduced by approximately 68 % in the combined system compared to the conventional ventilation system. Meslem et al [25] compared the innovative diffuser and the vortex diffuser with the same operating conditions in their study using the particle imaging velocity measurement (PIV) method. They revealed that the Coanda Effect and the jet effect disappear rapidly near the diffuser outlet in the vortex diffuser.…”
Section: Objectives/ Research Purposementioning
confidence: 99%
“…Meslem ve ark. [25], parçacık görüntüleme ile hız ölçümü (PIV) yöntemini kullandıkları çalışmalarında, aynı çalışma koşullarına sahip yenilikçi difüzör ile girdap difüzörü karşılaştırmışlar ve girdap difüzörde koanda etkisinin ve jet etkisinin difüzör çıkışının yakınında hızlıca yok olduğunu ortaya koymuşlardır. Çetin ve ark.…”
Section: Introductionunclassified